2016
DOI: 10.1039/c6cp00867d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent carbon nano dots from lignite: unveiling the impeccable evidence for quantum confinement

Abstract: Synthesizing nano carbon from its bulk precursors is of recent research interest. In this report, luminescent carbon nanoparticles (CNPs) with tunable particle size and surface functionality are fabricated from lignite using ethylenediamine as the reactive solvent and surface passivating agent via different experimental methods. From the steady-state and time-resolved photophysical studies of these differently sized CNPs, it is unveiled that the energy of the excitons generated after photoexcitation is quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…at 410 nm) when the concentration of GNDs was increased to 2.5 μg mL -1 At 5 μg mL -1 (Figure 6, bottom panel) we observed that the intrinsic state emission in the UV-deep blue region is nearly completely suppressed, as expected for a dispersion with a high concentration of GNDs. Such spectral changes, and in particular the redistribution of intensities between peaks in the PLE, are distinctive features of interchain states 92 and could not be explained by invoking self-absorption alone. Interchain states, either ground-state or excited-state complexes, could form between GND flakes, or GND flakes and species formed upon sonication of the o-DCB (also referred to as sono-polymers), or between o-DCB sono-polymers.…”
Section: Themselves This Observation Is Supported By the Lack Of A Cmentioning
confidence: 99%
“…at 410 nm) when the concentration of GNDs was increased to 2.5 μg mL -1 At 5 μg mL -1 (Figure 6, bottom panel) we observed that the intrinsic state emission in the UV-deep blue region is nearly completely suppressed, as expected for a dispersion with a high concentration of GNDs. Such spectral changes, and in particular the redistribution of intensities between peaks in the PLE, are distinctive features of interchain states 92 and could not be explained by invoking self-absorption alone. Interchain states, either ground-state or excited-state complexes, could form between GND flakes, or GND flakes and species formed upon sonication of the o-DCB (also referred to as sono-polymers), or between o-DCB sono-polymers.…”
Section: Themselves This Observation Is Supported By the Lack Of A Cmentioning
confidence: 99%
“…From this study one can infer that CND1 and CND2 might have a same chromophoric unit. However, the origin of multiexponential decays have been primarily attributed to ground state heterogeneity, i. e. the presence of multiple luminescence species ,. It can be mentioned here that even a single fluorophore present in a heterogeneous (polymeric) environment can also exhibit multi‐exponential fluorescence decays due to altered orientations and nature of accessible environment .…”
Section: Resultsmentioning
confidence: 90%
“…But the EMM of CN‐300 has one main peak at excitation/emission wavelengths (Ex/Em) of 320/390‐450 nm with an excitation‐dependent fluorescence behavior ( Figure b ). The observed fluorescence red‐shift of CN‐300 is accompanied with a significant reduction in photoluminescence intensity that is a signature of the gradual evolution of the confinement in quantum dots, similar to many carbon dots with wavelength‐dependent fluorescence behaviour . In contrast to CN‐300, CN‐250 displays a distinctive fluorescence performance.…”
Section: Resultsmentioning
confidence: 99%